Mobile intelligence - Yang, Laurence Tianruo; IEEE Xplore (Online Service); John Wiley & Sons (Hoboken, New Jersey : Wiley, 2010)
Cutting-edge research and application issues on computational intelligence in the mobile environment. The combination of mobile computing and computational intelligence, Mobile Intelligence focuses on learning patterns and knowledge from data generated by mobile users and mobile technology. As a very new area of research, mobile intelligence has created a wide range of opportunities for researchers, engineers, and developers to create new applications for both end users and businesses. Mobile Intelligence covers the comprehensive state-of-the-art in various applications of computational intelligence to the mobile paradigm, including mobile data intelligence, mobile mining, mobile intelligence security, mobile agent, location-based mobile information services, mobile context-aware and applications, intelligent networks, and mobile multimedia. Readers will not only learn different areas of mobile computing and its issues but also various intelligent approaches that contribute in addressing these issues, as well as discover other potential elements in the mobile paradigm.. Explains how to deliver benefits to a wide range of applications, including database query processing, multimedia, commerce systems, e-mail systems, search engines, and Web browsers. Covers efficient and effective mobile data retrieval by various advanced techniques and protocols. Describes intelligent approaches to resolving location-based query processing in the mobile environment. Discusses learning interesting patterns and knowledge out from data generated by mobile users. Investigates the deployment of mobile agents to support context-aware mobile applications. Presents intelligent solutions to the security issues in mobile networks. Evaluates advanced optimization methods for mobile multimedia retrieval. Reveals the latest techniques in solving various issues in wireless sensor network (WSN)Mobile Intelligence is geared for upper-level undergraduate and graduate students in computer science and data mining courses, as well as telecommunication engineers, mobile communication and networking engineers, computer scientists, computer engineers, mobile database specialists, and data mining specialists.
26. DDoS Attack Modeling and Detection in Wireless Sensor Networks -- 27. Energy-Efficient Pattern Recognition for Wireless Sensor Networks -- Index.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/21/2015.
Keywords: Mobile computing -- Research; Computational intelligence -- Research; Wireless communication systems -- Research; Electronic books